Prevalence and cause of loss of visual acuity and visual field in highly myopic eyes: the Beijing eye study - Jonas, Jost B.; Jonas, Rahul A.; Xu, Jie; Wang, Ya Xing (Ophthalmology, 2024)
Purpose - To explore the prevalence and causes of loss of visual acuity and visual field in highly myopic eyes. - Design - Population-based study. - Participants - 4439 subjects of the Beijing Eye Study underwent ophthalmological and systemic examinations including frequency doubling technology perimetry. - Methods - High myopia was defined by a refractive error of ≤-6 diopters (D) or axial length >26.0 mm. - Main Outcome Measures - Prevalence of vision impairment causes. - Results - 212 highly myopic eyes from 154 participants were included with a mean age of 56.2 ± 9.6 years, a mean refractive error of -9.87 ± 3.70 D and a mean axial length of 27.2 ± 1.3 mm. We observed moderate/severe vision impairment (MSVI) in 40 eyes (18.9%; 95% confidence interval [CI], 13.6-24.2) and blindness in 10 eyes (4.7%; 95% CI, 1.8-7.6). Primary causes for MSVI and blindness were myopic macular degeneration (MMD) (29/50; 58%), age-related macular degeneration (1/50; 2%), and branch macular retinal vein occlusion (1/50; 2%). Secondary causes were MMD (4/50; 8%) and optic nerve atrophy (14/50, 28%), further differentiated into non-glaucomatous optic atrophy (NGOA) (9/50; 18%) and glaucomatous optic atrophy (GOA) (5/50; 10%). Prevalence of MMD as vision impairment cause increased significantly from 1/61 (1.6%) in the refractive error group of -6.00 to ≥-7.00 D, to 16/25 (64%) in the group of <-15.0 D. Higher MMD prevalence correlated with higher myopic refractive error (P < 0.001) and increased likelihood of concomitant optic neuropathy (P < 0.001). Similarly, prevalence of optic neuropathy as vision impairment cause increased from 0/61 (0%) in the refractive error group of -6.00 D to ≥-7.00 D, to 9/25 (36%) in the group of <-15.0 D. Higher optic neuropathy prevalence correlated with more myopic refraction (P < 0.001) and older age (P = 0.02). - Conclusions - In this population-based recruited cohort of highly myopic patients, optic neuropathy accounted for vision impairment in 9.0% eyes, which was lower than the prevalence of MMD as vision impairment cause (18.9%). Notably, optic neuropathy became a significant contributor to vision impairment in more advanced high myopia, reaching 36% in the group with refractive error of <-15.0 D. - Financial Disclosure(s) - Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.